Qur'anic Ecofeminism: The Solution of Environmental Crisis - Atssania Zahroh; Mimi Suhayati (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2024)
This Qur'anic ecofeminism proposal is important because it can identify the cause of the environmental crisis from its very root: the concept of dualism. This qualitative research will employ Iceberg and U Theories to analyze that widespread concept. Hence, the present work aims to uncover the equilibrium between human beings and the environment inherent in the Qur’an and find its relevance to the wisdom tradition concept of Sachiko Murata. Our research concludes that, first, the dualism concept, which tends to separate subject and object, nature and human, men and women, contradicts tawhîd which is based on the vision of integration. This kind of vision is then, second, found being manifested in the so-called Qur’anic ecofeminism whose signs can be traced back through the Q.S 2:30; 2:60; 51:49; 38:27-28; 7:56 that all promote the aforementioned equilibrium spirit. Third, this kind of paradigm does not belong to persons unless fully aware of as the vicegerents (khalīfah) inheriting the wisdom tradition: those who see the correspondence between human beings and the environment more as a complementary rather than a subsidiary relationship.